The Effectiveness Of Regional Tax Revenue And Regional Retribution On Original Income Of The City Of Medan - Lores, Linda; Purnama Sari, Warsani; Utami, Tasya; Siregar, Retnawati; Laili, Isnainiah (Accounting and Business Journal, 2022)
This study aims to determine the effect of the effectiveness of local tax revenues and levies on local revenue in the city of Medan. The variables used in this study are the effectiveness of local tax revenues and the effectiveness of local retribution receipt local revenue. The type of research used is associative. The number of samples is 36 months during the period 2016-2018, with the sampling technique using a purposive sampling method. The type of data used in this research is quantitative data. The data source used in this research is secondary data. The data analysis technique used in this research is descriptive analysis and multiple linear regression analysis then hypothesis testing using the SPSS version 21. The results show that partially the Effectiveness of Regional Tax Revenue has a positive effect on Regional Original Income, the Effectiveness of R Revenue. Regional fees have a positive effect on Regional Original Income. Regional taxes and regional level related to regional development.